2011
DOI: 10.1002/j.2161-1874.2011.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Meditation in Addiction Counseling

Abstract: Meditation has been studied as a way of reducing stress in counseling clients since the 1960s. Alcoholics Anonymous, Narcotics Anonymous, and new wave behavior therapies incorporate meditation techniques in their programs. This article identifies meditation's curative factors and limitations when using meditation in addiction settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Both mental and physical well-being were found to have a positive effect of addiction recover behavior. Physical activities are known to increase the production dopamine, noradrenaline, and serotonin and can act as mechanisms for a natural high [31][32][33][34][35][36][37][38][39]. Many initiatives such as "lace-'em-up" have demonstrated the importance of physical activity for recovering addicts [40].…”
Section: Mental and Physical Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both mental and physical well-being were found to have a positive effect of addiction recover behavior. Physical activities are known to increase the production dopamine, noradrenaline, and serotonin and can act as mechanisms for a natural high [31][32][33][34][35][36][37][38][39]. Many initiatives such as "lace-'em-up" have demonstrated the importance of physical activity for recovering addicts [40].…”
Section: Mental and Physical Well-beingmentioning
confidence: 99%
“…Studies have shown that addition of exercise as a lifestyle change leads to abstinence or reduction in drug use [31][32][33][34]. Mediation and yoga has also been proved to help individuals in their withdrawals and addiction by acting a calming effect during their period of struggles [35][36][37]. Professional activities constitute another aspect of self-development.…”
Section: The Sem Model For Recoverymentioning
confidence: 99%
“…A simpler taxonomy was presented by Walsh and Shapiro (), who categorized meditation by the practice's type of attention (i.e., awareness‐based or concentrative), relationship with cognition (e.g., observing or modifying cognitions), and the goal (e.g., developing compassion or awareness). Following this further, Young, de Armas DeLorenzi, and Cunningham () divided all practices into three categories: (a) devotional (e.g., Christian practices), (b) mantra‐based (i.e., focused or unfocused), and (c) mindfulness‐based. Moreover, Ritz () highlighted the largest distinction between practices by separating them into the be here now meditations (e.g., those focused on creating present‐focused awareness) and the be there now meditations (e.g., those focused on transcendence and enlightenment).…”
Section: Types Of Meditationmentioning
confidence: 99%